Confectionary Sunflowers Cost-Return Budget (W-SF-F Rotation) in Western Kansas - O'Brien, Daniel M.; Dumler, Troy J. (My University, 2000)
This publication projects a budget that reflects expected income and costs based on typical production of dryland sunflower, both confectionary and oil type, in western Kansas.
MF937_2000_10
Keywords: MF937; Economics; Crops; MF